Die mittelalterlichen Handschriften des Stiftes Nonnberg in Salzburg - Hayer, Gerold; Schwembacher, Manuel; Glassner, Christine (2018)
This academic catalogue provides access for the first time to the medieval manuscripts and fragments preserved in the Benedictine Convent of Nonnberg in Salzburg: 108 manuscripts and 125 fragments from the early 9th to the middle of the 16th century